Revitalization of Plantation Strategic Policies to Promote Regional Competitiveness in South Kalimantan Province - Akbar, Sidderatul; Asmu’i, Asmu’i (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2016)
This study aims to identify and analyze the revitalization of strategic policies in the plantation sector to boost regional competitiveness in the province of South Kalimantan. The policies are in line with Nawacita Program, directing the futureagricultural development to achieve food sovereignty; so that Indonesia, as a nation, can manage and feed its people through food sovereignty. South Kalimantan is a province in Indonesia that relies on its regional income from mining and plantation sectors,after the mining (and quarrying) sector particularly coal mining, decreased. This study applies the action research approach based on Soft Systems Methodology with hybrid SWOT analysis at the mapping stage, focusing on the plantation policy revitalizationfor rubber and palm oil commodities during 2006 to 2015, since these two commodities are the most dominant commodities in South Kalimantan Province. The results show that it is necessary to do the re-formulation of strategic policies in the plantationsector, through the formulation of policy of Regional Regulation on Regional Budgets and National Medium-Term Development Plan (RPJMD) in plantation sector with emphasis on the harmonization of: (1) the Public Policy; (2) Technical Policy; (3) ResourceAllocation Policy; and (4) Financial Policy in South Kalimantan Province. These transformations should lead to: (1) Development of Cultivation and Protection of Regional Plantations; (2) Quality Development, Product Marketing and Resource Infrastructure,Eco-Friendly and Sustainable Plantation; and (3) Development of Professional and Responsible Mutual Performance Services. State of the art of this study is the importance of integrating the local wisdom and local wealth variables in revitalizing the strategicpolicies in the plantation sector in order to boost the regional competitiveness in the province of South Kalimantan that is in line with Central Government Policy of Nawacita Program to achieve food sovereignty.